2009
DOI: 10.1002/anie.200904156
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Blue Electrogenerated Chemiluminescence of Fluorene‐Substituted Aromatic Hydrocarbons

Abstract: Tailored molecular structure is the key to tune the electronic and spectroscopic properties of a molecule. This is always a goal in electrogenerated chemiluminescence (ECL), that is, to have a material with high photoluminescence (PL) quantum yield and stable, long-lived radical ions in solution upon oxidation and reduction. Among various ECL active materials, polyaromatic hydrocarbons (PAHs) were the earliest subjects of ECL studies, [1] and substituted PAHs have been widely investigated.[2] Indeed, the PAHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…However, the behavior of the redox couple ferrocene/ferricenium, used as internal standard, showed the same trend. Therefore, we can attribute the observed effect to the ohmic drop of the system, as previously reported for aprotic media by Bard and co-workers [69]. Furthermore, the peak current for both the redox processes under investigation increases linearly with the square root of the scan rate, as expected for a diffusion-controlled electrochemical process.…”
Section: Photophysical Characterization In Solutionsupporting
confidence: 85%
“…However, the behavior of the redox couple ferrocene/ferricenium, used as internal standard, showed the same trend. Therefore, we can attribute the observed effect to the ohmic drop of the system, as previously reported for aprotic media by Bard and co-workers [69]. Furthermore, the peak current for both the redox processes under investigation increases linearly with the square root of the scan rate, as expected for a diffusion-controlled electrochemical process.…”
Section: Photophysical Characterization In Solutionsupporting
confidence: 85%
“…Moreover, broad tailing above 430 nm can be observed, which is ascribed to the excimer of pyrene formed in MeCN : Bz (v/v ¼ 1 : 1). 12 It is clear that the maximum emission wavelength of Bz-Py is red-shied (by 33 nm) from Py, and is characterized by three dened vibrational structures around 407, 430, and 457 nm, which are similar to the vibrational structures observed in the PL spectrum of pyrene. The bump in the spectral line of Bz-Py around 480 nm is attributed to the Bz-Py excimer emission, which was conrmed in a previous report.…”
supporting
confidence: 56%
“…11 Bard's group reported that capping pyrene with two uorene derivatives produced new non-planar blue ECL materials and prevented excimer formation, resulting in enhanced ECL efficiency and stability of the cation radical. 12 Kaafarani et al combined carbazoles with pyrene and synthesized tortile tert-bis(carbazolyl) derivatives of pyrene and tetrahydropyrene, in a search for blue materials for organic electroluminescent devices. 13 However, not all nonplanar pyrene derivatives designed by the above strategies could completely suppress the tendency of the emission peak to undergo a red-shi in the PL/ECL process.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively in cases where this energy is not sufficient to populate the singlet state, ECL can be generated by triplet-triplet annihilation (T-route), which provides an alternate route to the emissive species in the singlet excited state. 9 Another ECL mechanism involves emission from an excited state dimer such as an excimer or exciplex (Eroute). 10-13 Exciplex emission is often encountered for aromatic molecules, including derivatives of thianthrene, 14 stilbene, 15 corannulene, 16 perylene, 17 anthracene, 18,19 and naphthalene 20 and is characterized by broad, structureless emission bands at long wavelengths.…”
Section: Introductionmentioning
confidence: 99%